2016
DOI: 10.1111/epi.13605
|View full text |Cite
|
Sign up to set email alerts
|

Functional properties of granule cells with hilar basal dendrites in the epileptic dentate gyrus

Abstract: SUMMARYObjective: The maturation of adult-born granule cells and their functional integration into the network is thought to play a key role in the proper functioning of the dentate gyrus. In temporal lobe epilepsy, adult-born granule cells in the dentate gyrus develop abnormally and possess a hilar basal dendrite (HBD). Although morphological studies have shown that these HBDs have synapses, little is known about the functional properties of these HBDs or the intrinsic and network properties of the granule ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Recent work suggests that axons which originate from a basal dendrite, rather than the soma, convey distinct properties to the parent cell (Thome et al, 2014; Kelly and Beck, 2017). We queried, therefore, the extent to which KO cells exhibit basal dendrite-originating axons.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work suggests that axons which originate from a basal dendrite, rather than the soma, convey distinct properties to the parent cell (Thome et al, 2014; Kelly and Beck, 2017). We queried, therefore, the extent to which KO cells exhibit basal dendrite-originating axons.…”
Section: Resultsmentioning
confidence: 99%
“…As explained above, our results suggest deficits in inhibition, but other anatomical or biophysical changes could be in play. For example, in individual mice with TLE, some GCs display pathological hilar basal dendrites that have been associated with increased intrinsic excitability that might allow them to fire bursts more easily (Kelly and Beck, 2017). It is also possible that there exist heterogeneity in GC mossy fiber sprouting, with some GCs receiving recurrent excitatory connections and some not.…”
Section: Discussionmentioning
confidence: 99%
“…Burst firing in the dentate gyrus has often been associated with pathological conditions such as epilepsy ( Shao and Dudek 2011 ; Dengler and Coulter 2016 ; Kelly and Beck 2017 ). However, recent in vivo recordings have shown that mature granule cells preferentially fire in bursts while animals are exploring a new environment ( Pernía-Andrade and Jonas 2014 ).…”
Section: Discussionmentioning
confidence: 99%